Composition of Diurnal Birds in the Buffer Zone around Kuala Lumpur International Airport, Malaysia - Zulkifli, Syaizwan Zahmir (2006)
Malaysia is known as one of the countries in the world to have a megadiversity status of flora and fauna. Its’ tropical forest has been formed for thousands of years until it reaches the current stability. The changes in the environment will alter the diversity of vertebrate populations including birds. Reports have highlighted that a combination of busy airports with large flocks and the proclivity of many birds to use airports for feeding, roosting and nesting activities has resulted in a risk of bird strike and creates an important safety issue for any airport (e.g., Cleary et al., 1999, Linnell et al., 1996). Therefore, a study of the bird composition in the buffer zone around KLIA was carried out. A total of 57 bird species from 28 families were identified. There were 38 species of birds that can be classified as resident species, 12 species of migratory birds and the remaining seven species were classified as resident and migrant. In general, bird population and diversity of birds was low compared to other type of forest around Malaysia. From the total bird species, 58% are fully protected and 12% are protected under Malaysian Wildlife Protection Act (1972). The remaining 30% are not under protection of the act. In terms of bird guilds, insectivores were dominant guild group with about 38% of the total 57 species observed, followed by piscivores (21%), grainivores (14%), omnivores (14%), carnivores (9%), nectarivores (2%) and frugivores (2%). In terms of the feeding habitats, 40% bird species were found to utilize the ground, 26% of bird species were found to use the water courses, 18% capture foods in the air, 9% found below canopy and the remaining 7% utilized the top canopy area. ANOVA showed there was a significant difference in number of bird individuals with respect to transects, daytime intervals and month groups respectively (P<0.05). The studies of total number of bird individuals and species richness showed both properties were higher in the morning (peak: 0930 hours observation period) and evening (peak: 1730 hours observation period) sessions. Lowest bird individuals and species richness can be detected at 1430 hours of the afternoon session. In terms of seasonal factor, bird individual and species richness were observed more in Mar-Apr 03 month group and the least was in Jul-Aug 02 and Jul-Aug 03 month groups. Most bird species were abundant in transect T11, T12, T1 and T7, however they were less abundant in transect T9 and T6. The Shannon –Wiener diversity index, H’, indicated that the buffer zone has a moderate status of bird diversity. The evenness, J’, study indicated that birds were most evenly distributed in transect T1 of May-Jun 03 month group, where as in transect T9 of Sep-Oct 02 month group, the J’ value was at the lowest point. The study also found 66 species of plants, which was expected to grow naturally in the wild, where as more than 25 species of plants were the man – planted. There were also 31 families and two suborders of insects had been sampled and identified. Coleoptera had the highest number of families. 19 species of insect were able to be identified up to the species level. There were two main groups existed in the buffer zone according to the number of bird individuals and species. Transect T11 and T12, T2 and T3, and T4 and T5 have the closest similarity distance between each pair. It can be concluded that at the moment, bird’s population, behaviour, distribution and habitat selection do not posses any serious threats to aircraft services at KLIA. Further and continuous studies are suggested in order to produce an effective guideline for tropical bird strike prevention strategies.